Do health behaviours change after colonoscopy? A prospective cohort study on diet, alcohol, physical activity and smoking among patients and their partners. Issue 1 (14th January 2014) - Hubbard, Gill; Brown, Alistair; Campbell, Anna; Campbell, Neil; Diament, Bob; Fielding, Shona; Forbat, Liz; Masson, Lindsey F; O'Carroll, Ronan; Stein, Kevin; Morrison, David S
Abstract : Objectives: To describe diet, alcohol, physical activity and tobacco use prospectively, that is, before and 10 months after colonoscopy for patients and their partners. Design: Prospective cohort study of health behaviour change in patients and partners. Comparison groups are patients receiving a normal result notification (NRN) versus patients receiving an abnormal result notification (ARN). Patients and partners (controls) are also compared. Setting: 5 Scottish hospitals. Participants: Of 5798 colonoscopy registrations, 2577 (44%) patients met the eligibility criteria of whom 565 (22%) were recruited; 460 partners were also recruited. Measures: International Physical Activity Questionnaire, Scottish Collaborative Group Food Frequency Questionnaire (includes alcohol), smoking status, sociodemographic characteristics, body mass index, medical conditions, colonoscopy result, Multidimensional Health Locus of Control Scale, behaviour-specific self-efficacy scales. Results: 57% of patients were men, with a mean age of 60.8 years (SE 0.5) and 43% were from more affluent areas. 72% (n=387) of patients received an ARN and 28% (n=149) received an NRN. Response rate of the second questionnaire was 68.9%. Overall, 27% of patients consumed <5 measures of fruit and vegetables/day, 20% exceeded alcohol limits, 50% had low levels of physical activity and 21% were obese. At 10-month follow-up, a 5% reduction in excessive alcohol consumption and an 8% increase in low levels of physical activity were observed among patients; no significant changes occurred in partners. Baseline high alcohol consumption and low physical activity were the strongest predictors of these behaviours at follow-up. Low alcohol self-efficacy and increasing age were associated with poorer health-related behaviours at follow-up for alcohol consumption and physical activity, respectively. Conclusions: Colonoscopy is associated with marginal beneficial changes in some behaviours but not others. Further work is needed to explore how services can optimise increases in beneficial behaviours and mitigate increases in harmful ones. Registrations: REC REF 10/S0709/24, UKCRN 9911.